Implications of BRAF V600E mutation in gliomas: Molecular considerations, prognostic value and treatment evolution - Di Nunno, Vincenzo; Gatto, Lidia; Tosoni, Alicia; Bartolini, Stefania; Franceschi, Enrico (Frontiers in Oncology, 2023)
Gliomas are molecularly heterogeneous brain tumors responsible for the most years of life lost by any cancer. High-grade gliomas have a poor prognosis and despite multimodal treatment including surgery, radiotherapy, and chemotherapy, exhibit a high recurrence rate. There is a need for new therapeutic approaches based on precision medicine informed by biomarker assessment and BRAF, a key regulator of MAPK signaling pathway, influencing cell differentiation, proliferation, migration and pro-tumorigenic activity, is emerging as a promising molecular target. V600E, is the most frequent BRAF alteration in gliomas, especially in pediatric low-grade astrocytomas, pleomorphic xanthoastrocytoma, papillary craniopharyngioma, epithelioid glioblastoma and ganglioglioma. The possible application of BRAF-targeted therapy in gliomas is continuously growing and there is preliminary evidence of prolonged disease control obtained by BRAF inhibitors in tumors harboring BRAF V600E mutation. The possibility of introducing targeted therapies into the treatment algorithm represents a paradigm shift for patients with BRAF V600E mutant recurrent high-grade and low-grade glioma and BRAF routine testing should be considered in clinical practice. The focus of this review is to summarize the molecular landscape of BRAF across glioma subtypes and the novel therapeutic strategies for BRAF V600E mutated tumors.